Dopamine transporter imaging predicts clinically‐defined α‐synucleinopathy in REM sleep behavior disorder. Issue 1 (15th December 2020) - Chahine, Lana M.; Brumm, Michael C.; Caspell‐Garcia, Chelsea; Oertel, Wolfgang; Mollenhauer, Brit; Amara, Amy; Fernandez‐Arcos, Ana; Tolosa, Eduardo; Simonet, Cristina; Hogl, Birgit; Videnovic, Aleksandar; Hutten, Samantha J.; et al.
Abstract: Introduction: Individuals with idiopathic rapid eye movement sleep behavior disorder (iRBD) are at high risk for a clinical diagnosis of an α ‐synucleinopathy (aSN). They could serve as a key population for disease‐modifying trials. Abnormal dopamine transporter (DAT) imaging is a strong candidate biomarker for risk of aSN diagnosis in iRBD. Our primary objective was to identify a quantitative measure of DAT imaging that predicts diagnosis of clinically‐defined aSN in iRBD. Methods: The sample included individuals with iRBD, early Parkinson's Disease (PD), and healthy controls (HC) enrolled in the Parkinson Progression Marker Initiative, a longitudinal, observational, international, multicenter study. The iRBD cohort was enriched with individuals with abnormal DAT binding at baseline. Motor and nonmotor measures were compared across groups. DAT specific binding ratios (SBR) were used to calculate the percent of expected DAT binding for age and sex using normative data from HCs. Receiver operative characteristic analyses identified a baseline DAT binding cutoff that distinguishes iRBD participants diagnosed with an aSN in follow‐up versus those not diagnosed. Results: The sample included 38 with iRBD, 205 with PD, and 92 HC who underwent DAT‐SPECT at baseline. Over 4.7 years of mean follow‐up, 14 (36.84%) with iRBD were clinically diagnosed with aSN. Risk of aSN diagnosis was significantly elevated among those with baseline putamen SBR ≤ 48% of that expected for age and sex, relative to those above this cutoff (hazard ratio = 17.8 [95%CI: 3.79–83.3], P = 0.0003). Conclusion: We demonstrate the utility of DAT SBR to identify individuals with iRBD with increased short‐term risk of an aSN diagnosis.